COMPARISON OF THE EFFECTIVENESS OF DIFFERENT OVULATION STIMULATION PROGRAMS - Shopulotova , Z.A.; Khudoyarova , D.R. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
The article presents a comparative study of the effectiveness of ovulation stimulation programs: modified natural cycle (MNC) and standard short protocol in the context of in vitro fertilization (IVF). The study involved 60 patients divided into two groups (30 people each). The main group (MNC) demonstrated superiority in key performance indicators (ovulation frequency, number of mature follicles), but the gynecological history of patients in the control group (standard protocol) was characterized by greater severity (PCOS, endometriosis, decreased ovarian reserve). It was found that the modified natural cycle is the optimal choice for patients with male factor infertility or without complicated gynecological/somatic pathology, due to the minimal hormonal load and physiological synchronization of processes. In cases with complicated gynecological status, the use of standard protocols ensuring control of the multifollicular response is recommended. The authors emphasize the need for further research to develop personalized protocol selection algorithms taking into account multidimensional parameters: age, ovarian reserve, comorbid conditions and biomarkers. The results of the work indicate the importance of patient stratification and the integration of precision approaches into reproductive medicine.